Risk Plan Linen Rental Laundry with RFID Technology PT Think Clean Laundry - Theresia V Siagian; Rhian Indradewa; Sukmo Hadi Nugroho; Muhammad Dhafi Iskandar (Publikasi Indonesia, 2024)
The Risk Plan Study for PT Think Clean Laundry aims to ensure the company's vision is executed as planned and minimizes potential risks. The plan includes short-, medium–, and long-term goals, objectives, and risk management principles based on ISO 31000:2018. The Risk Management Framework is explained through leadership, commitment, integration, design, implementation, evaluation, and continuous improvement. The risk management process includes risk identification, assessment, analysis, evaluation, handling, communication, consultation, monitoring, review, recording, and reporting. The main objective of this plan is to identify, evaluate, and manage risks that may arise in the company's operations, including business, financial, and quality risks. By implementing structured and comprehensive risk management, PT Think Clean Laundry is committed to improving operational effectiveness and efficiency and complying with applicable regulations.